MENGEMBANGKAN SOFT SKILLS GURU UNTUK MENDIDIK AKHLAK MULIA SISWA - Ach Saifullah (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2020)
Soft Skills are the non-technical abilities that a person possesses when dealing with himself (intra-personal skills) and others (inter-personal skills). While morals are the nature of deeds that have been embedded and rooted very strongly in a person so that to do it will be easy and easy without any thoughts and considerations. The role and duties of teachers are not limited to transferring knowledge. Personality competence and social competence are needed as soft competences to educate students' morals. This shows that the soft skills of a teacher become software that always accompanies the learning process.